2012
DOI: 10.1186/1556-276x-7-161
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on single-layer reduced graphene oxide films obtained by electrochemical reduction and hydrazine vapor reduction

Abstract: The comparison between two kinds of single-layer reduced graphene oxide (rGO) sheets, obtained by reduction of graphene oxide (GO) with the electrochemical method and hydrazine vapor reduction, referred to as E-rGO and C-rGO, respectively, is systematically studied. Although there is no morphology difference between the E-rGO and C-rGO films adsorbed on solid substrates observed by AFM, the reduction process to obtain the E-rGO and C-rGO films is quite different. In the hydrazine vapor reduction, the nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 56 publications
3
48
0
Order By: Relevance
“…[ 279 ] Different kinds of carbon materials were studied in their work, such as the thermally exfoliated graphite, graphene from the chemically C-rGO surface than that on the E-rGO, which caused the server nonselective adsorption/desorption of analyte molecules on the C-rGO. [ 124 ] In addition, a comparison study carried out by Giovanni et al used GO, E-rGO and thermally reduced GO (T-rGO) in the impedimetric sensing of DNA. [ 196 ] Their results indicated that the GO electrode can lead to a better discrimination among the three different ssDNA targets than does the E-rGO or the T-rGO electrode.…”
Section: Carbon-based Electrodesmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 279 ] Different kinds of carbon materials were studied in their work, such as the thermally exfoliated graphite, graphene from the chemically C-rGO surface than that on the E-rGO, which caused the server nonselective adsorption/desorption of analyte molecules on the C-rGO. [ 124 ] In addition, a comparison study carried out by Giovanni et al used GO, E-rGO and thermally reduced GO (T-rGO) in the impedimetric sensing of DNA. [ 196 ] Their results indicated that the GO electrode can lead to a better discrimination among the three different ssDNA targets than does the E-rGO or the T-rGO electrode.…”
Section: Carbon-based Electrodesmentioning
confidence: 99%
“…Recently, we carried out a comparison study on electrochemically-reduced GO (E-rGO) and hydrazine-reduced GO (C-rGO) sheets and found that the electrochemical method is more effective to reduce GO fi lms compared to the hydrazine vapor reduction method. [ 124 ] In addition, when the E-rGO and C-rGO electrodes were used to detect dopamine (DA) in the presence of uric acid (UA) and ascorbic acid (AA), their electrochemical sensing results were quite different. By using the E-rGO electrode, the independent electrochemical oxidation of each analyte was observed, evidenced by the well-defi ned oxidation peaks for AA, DA, and UA.…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…95,124 To reduce the graphenes, it is taking force the electrochemical method, instead of the chemical one, because it is easy, fast, efficient and clean technique compared with the chemical method. Electrochemical sensors based on reduced graphene have shown electrochemical catalytic activity towards a variety of products 125,126 . Zheng et al studied the simultaneous oxidation of 5-mC and C on electrochemically reduced graphene-modified GC electrodes which enhanced the signal 11.9 and 3.3 times with respect to those obtained with bare GC.…”
Section: Graphenesmentioning
confidence: 99%
“…The experiment results reveal that the electrochemical approach is a relatively economic, fast and environmental friendly method to prepare graphene avoiding toxic and hazardous chemicals such as hydrazine or dimethylhydrazine in the reduction process [15].…”
Section: Introductionmentioning
confidence: 98%